Transformasi Permukiman Kumuh Melalui Konsep Kampung Vertikal Berbasis Potensi Sosial dan Lingkungan di Kampung Aur, Medan - Muhammad, Fadri; Maulana, Sherlly (Universitas Medan Area, 2025)
Slum settlements remain a global challenge requiring localized and sustainable interventions. Kampung Aur, located in Medan City along the Deli River, is one such densely populated urban area classified as a slum. Considering its environmental risks, social conditions, and flood vulnerability, this study aims to formulate a vertical kampung (vertical village) strategy as a renewal solution rooted in the community’s local character. A qualitative descriptive method was employed, using field observations, interviews, and spatial analysis in Neighborhood Units III and IV. The findings highlight Kampung Aur’s strategic potential in terms of historical value, socio-cultural resilience, and proximity to urban and commercial centers, which make it a viable candidate for vertical upgrading. Four alternative massing models are proposed—low-rise blocks, high-rise slabs, courtyard and tower, and high-rise cluster—each assessed for spatial efficiency, ventilation, flood resistance, and livability. The study further recommends integrated strategies including improved microclimate design, green open spaces, and functional zoning to enhance social interaction and environmental resilience. In conclusion, vertical kampung development represents a context-sensitive transformation strategy for waterfront slum areas. Its success relies on participatory planning, socio-economic empowerment, and the preservation of local identity within a sustainable and inclusive urban framework.